Sun proteins and Dpy19l2 forming LINC-like links are critical for spermiogenesis - Ray, Pierre F. (Biol Open, 2016)
Summary: In this response to Pasch et al.’s (2015) discovery that Sun4 is essential for sperm head formation, the authors highlight that like Sun4, Dpy19l2 has a likely LINK-like function and that it also plays a crucial role in spermiogenesis and male infertility.